From incarceration to successful reintegration : an ethnographic study of the impact of a halfway house on recidivism amongst female ex-offenders - Van Wyk, Stephanie Anne (Stellenbosch : Stellenbosch University, 2014)
Thesis (MA)--Stellenbosch University, 2014.